4-Ethoxy-N-(6-methylquinolin-2-ylmethylene)aniline - Aygün, M; Isik, S; Turgut, Z; Özbey, S; Kendi, E (MUNKSGAARD INT PUBL LTD, 1999)
The crystal structure of the title Schiff base, C19H18N2O, has been determined. The 6-methylquinoline group and formimidoyl moiety are almost planar, and the dihedral angle between the planes of ethoxyphenyl and 6-methylquinoline is 44.02 (8)degrees. The crystal structure is stabilized by intramolecular and intermolecular hydrogen bonds of the C-H ... N type forming a chain extending in the a direction.
Keywords: SCHIFF; Chemistry; Crystallography